Impact of Sea‐Ice Dynamics on the Spatial Distribution of Diatom Resting Stages in Sediments of the Pacific Arctic Region. Issue 7 (8th July 2021) - Fukai, Yuri; Matsuno, Kohei; Fujiwara, Amane; Suzuki, Koji; Richlen, Mindy L.; Fachon, Evangeline; Anderson, Donald M.
Abstract: The Pacific Arctic region is characterized by seasonal sea‐ice, the spatial extent and duration of which varies considerably. In this region, diatoms are the dominant phytoplankton group during spring and summer. To facilitate survival during periods that are less favorable for growth, many diatom species produce resting stages that settle to the seafloor and can serve as a potential inoculum for subsequent blooms. Since diatom assemblage composition is closely related to sea‐ice dynamics, detailed studies of biophysical interactions are fundamental to understanding the lower trophic levels of ecosystems in the Pacific Arctic. One way to explore this relationship is by comparing the distribution and abundance of diatom resting stages with patterns of sea‐ice coverage. In this study, we quantified viable diatom resting stages in sediments collected during summer and autumn 2018 and explored their relationship to sea‐ice extent during the previous winter and spring. Diatom assemblages were clearly dependent on the variable timing of the sea‐ice retreat and accompanying light conditions. In areas where sea‐ice retreated earlier, open‐water species such as Chaetoceros spp. and Thalassiosira spp. were abundant. In contrast, proportional abundances of Attheya spp. and pennate diatom species that are commonly observed in sea‐ice were higher in areas where diatoms experienced higher light levels and longer day length in/under the sea‐ice. This study demonstrates that sea‐ice dynamics are an important determinant of diatom species composition and distribution in the Pacific Arctic region. Plain Language Summary: The Pacific Arctic region is characterized by seasonal sea‐ice, and there is considerable interannual variation in the timing and quality of ice presence. In this region, diatoms are the dominant phytoplankton group during spring and summer. Under conditions unfavorable for growth, such as low light or limiting nutrients, many diatom species produce resting stages that are similar to "seeds" of plants. These resting stages settle to the seafloor and can reflect the diatom assemblages in the overlying water column. Since diatom species distribution is closely related to sea‐ice dynamics, detailed studies of this relationship are fundamental to understanding the basis of marine ecosystems in the Pacific Arctic region. In this study, we explored the relationship by comparing the distribution of diatom resting stage assemblages with patterns of sea‐ice coverage. Diatom assemblages detected in sediments were dependent on the variable timing of the sea‐ice retreat and accompanying light conditions. In areas where sea‐ice retreated earlier, open‐water species were abundant, while proportional abundances of ice‐associated diatoms were higher in areas where diatoms experience favorable light conditions in/under the sea‐ice. This study demonstrates that sea‐ice dynamics are an important determinant of diatom composition in the Pacific Arctic region. Key Points: Diatom resting stage assemblages were quantified and their relationship to the sea‐ice dynamics in the Pacific Arctic region was explored Diatom composition follows spatial patterns that depend upon the variable timing of sea‐ice retreat and accompanying light conditions Abundance of resting stage diatom cells in sediments varied by several orders of magnitude across the study region